Prevalence of BRCA1 and BRCA2 mutations in non-familial breast cancer patients with high risks in Korea: The Korean Hereditary Breast Cancer (KOHBRA) Study - Son, Byung Ho (Springer US, 2012)
Prevalence and phenotype of BRCA mutation can vary by race. The purpose of this study is to evaluate the prevalence of BRCA1/2 mutations in non-familial breast cancer patients with high risks in Korea. A subset of 758 patients was selected for this study from the KOHBRA nationwide multicenter prospective cohort study. Mutations in BRCA1/2 genes were tested using fluorescent-conformation sensitive gel electrophoresis, denaturing high performance liquid chromatography or direct sequencing. Mutation of BRCA1/2 genes were identified in 65 (8.6%) patients among total 758 patients [BRCA1 mutation: 25 (3.3%), BRCA2 mutation: 40 (5.3%)]. According to risk groups, mutation of BRCA1/2 genes were identified in 53 (8.5%) of 625 early onset patients (age ≤40), in 22 (17.7%) of 124 bilateral breast cancer patients, in 3 (50.0%) of 6 breast and ovarian cancer patients, in one (5.9%) of 17 male breast cancer patients, in 5 cases (7.6%) of 66 multiple organ cancer patients. The most common mutation was 509C>A for BRCA1 and 7708C>T for BRCA2. The prevalence of BRCA1/2 mutations by age in early onset patients was significantly different (age <35 vs age ≥35; 10.0 vs 2.9%, p = 0.0007). BRCA1/2 mutations for non-familial Korean breast cancer patients were detected at a high rate, particularly, in patients with early onset of less than 35 years of age, bilateral breast cancer, and breast and ovarian cancer. Individualized genetic counseling should be offered for non-familial breast cancer patients with these risk factors.